Etiology and risk factors among young patients presenting with stroke in a tertiary care hospital in South India - Subburaj, Thiagaraj; Kumarasamy, Subramaniyan; Velayudam, Sundaravadivelu (International Journal of Research in Medical Sciences, 2017)
Background: Stroke is one of the leading causes of disease and death throughout the world with the incidence rising steeply with age. The occurrence of stroke in young is rare but once it occurs the outcome is severe. Limited studies have been performed in the Indian population to describe the clinical presentation and etiology of young adults with stroke. The objective of present study is to assess the etiology, risk factors and clinical presentation among patients who visit a tertiary care centre with a clinical diagnosis of stroke in individuals less than 45 years of age. Methods: Consecutive patients visiting the Dept of General Medicine & Neurology, SRM Hospital aged between 15-45 years with abrupt onset of focal or global neurological deficit attributable to vascular cause and persisting for more than 24 hours were included into the study. Patients with traumatic injury and transient ischemic attack were excluded. The clinical features, laboratory and radiological investigations were obtained from the patient’s records. Results: The mean age of the study group was 36.42±6.92 years. The most common risk factor amongst study subjects was smoking (36%). Hemiplegia was more commonly seen in males (38 vs. 14 %, p= 0.26) than in females. Seizures were more commonly seen among subjects with hemorrhagic stroke and cortical venous thrombosis (p= 0.001). Among subjects with ischemic stroke, the most common etiology was hypercoagulation. The most common arterial territory involved was Middle cerebral artery territory 84.84% with the Left MCA (53.5%) being more common than right MCA (46.4%). Conclusions: The clinical presentation and etiology among young patients with stroke appear to remain consistent with that reported earlier in the literature. The paucity of rare presentations of stroke in our study could be attributable to the limited sample size of our study.